Detection of antibody-secreting cells specific for the cytomegalovirus and herpes simplex virus surface antigens - Alt, Mira; Falk, Jessica; Eis-Huebinger, Anna Maria; Kropff, Barbara; Sinzger, Christian; Krawczyk, Adalbert (Journal of Immunological Methods, 2018)
Infections with the herpes simplex virus (HSV) and the human cytomegalovirus (HCMV) can lead to life-threatening diseases, particularly in immunosuppressed patients. Furthermore, HSV infections at birth (herpes neonatorum) can result in a disseminated disease associated with a fatal multiorgan failure. Congenital HCMV infections can result in miscarriage, serious birth defects or developmental disabilities. Antibody-based interventions with hyperimmunoglobulins showed encouraging results in clinical studies, but clearly need to be improved. The isolation of highly neutralizing monoclonal antibodies is a promising strategy to establish potent therapy options against HSV and HCMV infections. Monoclonal antibodies are commonly isolated from hybridomas or EBV-immortalized B-cell clones. The screening procedure to identify virus-specific cells from a cell mixture is a challenging step, since most of the highly neutralizing antibodies target complex conformational epitopes on the virus surface. Conventional assays such as ELISA are based on purified viral proteins and inappropriate to display complex epitopes. To overcome this obstacle, we have established two full-virus based methods that allow screening for cells and antibodies targeting complex conformational epitopes on viral surface antigens. The methods are suitable to detect surface antigen-specific cells from a cell mixture and may facilitate the isolation of highly neutralizing antibodies against HSV and HCMV.
EVALuna2:35357